Features of Urdu Literary Review - Shakeel Ahmad (Zaban-o-Adab, 2023)
Urdu Literary Review writing is the foundation of Urdu literary criticism. Its history is not as old as the tradiation of Urdu literature. Hali, with Sir Sayyed and Waheedu-Din Saleem, is the first critic and Literary Review writer. This study is not a new attempt nor primarily a new exegesis in the field of Literary Review writing but a sustained reflection on the basic principles and criteria of its features and canvas by analysing its style, contents and tradition. This study raises the questions whether Urdu Literary Review writing is relevant to the demands and expectations of the present age and the reader and assist both of them. This paper marks the basic trends of Review writing, its merits and demerits. In the this paper qualitative research has been followed. Literary research designe and Internet sources are consulted. The future researchers can make a comparison/contrast of Urdu Literary Review writing with the Literary reviews of other languages.